1995
DOI: 10.1177/000331979504600301
|View full text |Cite
|
Sign up to set email alerts
|

Arteriographic Morphology and Intracoronary Thrombus in Patients with Unstable Angina, Non-Q Wave Myocardial Infarction and Stable Angina Pectoris

Abstract: Coronary artery lesions were compared in 71 patients with unstable angina, 15 patients with non-Q wave myocardial infarction (MI), and 40 patients with stable angina. In the unstable angina group, 29 patients had new-onset angina, 31 had crescendo angina, and 11 had rest angina. In a subgroup of patients with unstable angina, three-vessel disease was less frequently (P < 0.05) seen in patients with new-onset angina (10.3%) than in the patients with crescendo angina (51.6%) or rest angina (54.5%). An angina-pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Although the optimal treatment regimen or strategies for such patients is under investigation, a proposed diagnostic schema is presented in Figure 2 and a therapeutic approach is depicted in revised AMI accompanied by nondiagnostic ECG changes is believed to be related to acute disruption of an atherosclerotic plaque in the setting of chronic inflammatory infiltration of its fibrous cap; this underlying pathophysiology is not thought to differ from AMI accompanied by ST-segment elevation. As more angiographic and clinical correlation studies are done, it is becoming clear that total occlusion of the culprit vessel is much less common in AMI without ST-segment elevation than in MI with ST elevation (82,(138)(139)(140). Furthermore, patients without ST-segment elevation are more likely to have multivessel disease and prior MIs than are those with ST-elevation MI (810).…”
Section: Classmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the optimal treatment regimen or strategies for such patients is under investigation, a proposed diagnostic schema is presented in Figure 2 and a therapeutic approach is depicted in revised AMI accompanied by nondiagnostic ECG changes is believed to be related to acute disruption of an atherosclerotic plaque in the setting of chronic inflammatory infiltration of its fibrous cap; this underlying pathophysiology is not thought to differ from AMI accompanied by ST-segment elevation. As more angiographic and clinical correlation studies are done, it is becoming clear that total occlusion of the culprit vessel is much less common in AMI without ST-segment elevation than in MI with ST elevation (82,(138)(139)(140). Furthermore, patients without ST-segment elevation are more likely to have multivessel disease and prior MIs than are those with ST-elevation MI (810).…”
Section: Classmentioning
confidence: 99%
“…©1999 by the American College of Cardiology and the American Heart Association, Inc. elevation, total coronary occlusion is much less common. 82,[138][139][140] In the initial study by DeWood et al,82 total coronary occlusion occurred in only 32% of patients studied early by angiography, a greater than 70% stenosis was present in more than 70%, and a few had normal coronary arteries. When total occlusion is present, it most commonly occurs in the circumflex distribution, which is electrocardiographically silent, or in a vessel that is well collateralized.82, 141 The earlier descriptions of MI patient populations often differ from more contemporary descriptions.…”
mentioning
confidence: 98%
“…Unstable angina pectoris (UAP) is the subset of acute coronary syndromes (ACS) caused by the erosion or rupture of atherosclerotic plaque and thrombosis. 1 , 2 The prevalence of coronary thrombus has been estimated at 10% to 80% in patients with UAP. 3 Primary therapy is often urgently needed and/or involves elective percutaneous coronary intervention (PCI).…”
Section: Introductionmentioning
confidence: 99%
“…Although variable in its pathobiologic predominance of platelets and fibrin and rarely of sufficient mass to fully or permanently occlude an epicardial coronary vessel, the derangement of coronary artery blood flow is capable of compromising myocardial perfusion for a critical period. [1][2][3][4] Early descriptions suggested that patients with non-ST-segment elevation MI, compared with those with ST-segment elevation or bundle branch block MI, represent a homogeneous population whose risk for adverse clinical outcomes, including recurrent myocardial ischemia, infarction, and cardiac death, was uniform and greatest in the weeks to months following hospital discharge [5][6][7][8][9][10] ; however, more recent observations have challenged the belief that patients are generally at low risk during the early postinfarction period. 11 An ability to risk characterize patients represents an important step toward developing targeted and cost-effective management strategies for wide-scale implementation.…”
mentioning
confidence: 99%